2015
DOI: 10.1128/aac.00229-15
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Tobramycin Analogues as Antibacterial and Antifungal Agents

Abstract: In this study, we investigated the in vitro antifungal activities, cytotoxicities, and membrane-disruptive actions of amphiphilic tobramycin (TOB) analogues. The antifungal activities were established by determination of MIC values and in time-kill studies. Cytotoxicity was evaluated in mammalian cell lines. The fungal membrane-disruptive action of these analogues was studied by using the membrane-impermeable dye propidium iodide. TOB analogues bearing a linear alkyl chain at their 6؆-position in a thioether l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 39 publications
8
88
0
Order By: Relevance
“…We also observed that all of our bisbenzimidazole derivatives displayed no activity (≥31.2 µg/mL) against A. flavus ATCC MYA-3631 (strain K ). As we and others previously discovered that the addition of long alkyl chains to aminoglycosides such as kanamycin A (KANA), 34 kanamycin B (KANB), 12, 35 and tobramycin (TOB) 11, 13 results in killing of fungal cells through membrane perturbation, we decided to functionalize the bisbenzimidazole core with various alkyl chains hoping for an additive action against fungal growth. The divergent synthetic strategy allowed us to introduce various alkyl chains on either side of the molecule efficiently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that all of our bisbenzimidazole derivatives displayed no activity (≥31.2 µg/mL) against A. flavus ATCC MYA-3631 (strain K ). As we and others previously discovered that the addition of long alkyl chains to aminoglycosides such as kanamycin A (KANA), 34 kanamycin B (KANB), 12, 35 and tobramycin (TOB) 11, 13 results in killing of fungal cells through membrane perturbation, we decided to functionalize the bisbenzimidazole core with various alkyl chains hoping for an additive action against fungal growth. The divergent synthetic strategy allowed us to introduce various alkyl chains on either side of the molecule efficiently.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, our group has been actively involved in developing novel small molecules as well as aminoglycoside-based antifungal agents to treat both topical and systemic fungal infections. 1113 Based on a recent report, a high-throughput screening of more than 100,000 individual compounds with heterocyclic cores, in the presence fungal pathogens, led to the identification of a promising benzimidazole scaffold. 14 …”
Section: Introductionmentioning
confidence: 99%
“…While compounds 3a – j , l , m , p – t , jj , and kk have been described previously, [1314] compounds 3k , n , o , and u – ii are new. Our collection encompasses a diverse set of 6″-substituents, including linear, branched, and cyclic alkyl groups, and substituted aromatic rings.…”
mentioning
confidence: 99%
“…In most cases, the overall yields of syntheses are rather low, requiring large quantities of starting materials and many steps to achieve a single product. With the challenges in synthesizing AGs from scratch, several approaches have targeted modifying currently approved AGs including modifications at various positions such as the 1-, 6′-, 21 2″-, 22 5″-, 23 and 6″-positions, 3,24,25 dimerization, 26,27 and covalent attachment to other antibiotics, 23,28 which have all had varying degree of success. Herein, we report on the facile syntheses of AMK, kanamycin A (KAN), netilmicin (NET), sisomicin (SIS), and tobramycin (TOB) mono-and dimodified at the 1-, 6′-, and/or 4‴-amines by glycinyl, carboxybenzyl, and AHB moieties (Scheme 1).…”
mentioning
confidence: 99%
“…1 More recently, AGs have also been investigated as potential antifungal agents and as a treatment option for genetic disorders associated with premature termination codons. 2,3 The manifestation of a number of resistance mechanisms that reduce the efficacy of AGs is a major obstacle in the development of novel members of this family of antibiotics. Examples of resistance mechanisms include increased efflux or decreased uptake of AGs by bacterial cells, 4 modifications of the 16S rRNA, 5 and acquisition of AG-modifying enzymes (AMEs) by the bacteria.…”
mentioning
confidence: 99%